How Well Do Health-Mediation Programs Address the Determinants of the Poor Health Status of Roma? A Longitudinal Case Study - Belak, Andrej; Veselska, Zuzana Dankulincova; Geckova, Andrea Madarasova; Dijk, Jitse P van; Reijneveld, Sijmen A (International journal of environmental research and public health, 2017)
In Central and Eastern Europe (CEE), health-mediation programs (HMPs) have become central policy instruments targeting health inequities between segregated Roma and general populations. Social determinants of health (SDH) represent the root causes behind health inequities. We therefore evaluated how an HMP based in Slovakia addressed known SDH in its agenda and its everyday implementation. To produce descriptive data on the HMP's agenda and everyday implementation we observed and consulted 70 program participants across organizational levels and 30 program recipients over the long-term. We used a World Health Organization framework on SDH to direct data acquisition and consequent data content analysis, to structure the reporting of results, and to evaluate the program's merits. In its agenda, the HMP did not address most known SDH, except for healthcare access and health-related behaviours. In the HMP's everyday implementation, healthcare access facilitation activities were well received, performed as set out and effective. The opposite was true for most educational activities targeting health-related behaviours. The HMP fieldworkers were proactive and sometimes effective at addressing most other SDH domains beyond the HMP agenda, especially material conditions and psychosocial factors, but also selected local structural aspects. The HMP leaders supported such deliberate engagement only informally, considering the program inappropriate by definition and too unstable institutionally to handle such extensions. Reports indicate that the situation in other CEE HMPs is similar. To increase the HMPs' impact on SDH, their theories and procedures should be adapted according to the programs' more promising actual practice regarding SDH.
Keywords: Slovenská republika; podpora zdraví; zdravotní stav; programy národního zdraví; Romové; sociální determinanty zdraví; Social Determinants of Health; Humans; Longitudinal Studies; longitudinální studie; Health Status; National Health Programs; lidé; Roma; Health Promotion; Slovakia